Dynamics and stability results of fractional integro-differential equations with complex order - Vivek, D.; Kanagarajan, K.; Harikrishnan, S. (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper, we study the existence, uniqueness and Ulam stability of solutions of fractional integro-differential with complex order. Based on Krasnoselkii fixed point theorem and Banach contraction principle, we obtain existence and Ulam stability results.